On Centraloid Operators - As’ad, As’ad Y. (Journal of Informatics and Mathematical Sciences, 2012)
In this paper we study centraloid operators, some of their properties and their relation to their adjoint, their Hilbert adjoint, isometries and normal operators. Also we show that the set of all centraloid operators need not be a Banach algebra.